Pengaruh Rasa Saling Percaya Terhadap Kolaborasi - Robbi Saepul Rahman (Majalah Bisnis & IPTEK, 2019)
Research on mutual trust and collaboration has been proven by previous studies that show positive and constructive behavior related to work. Some studies use instruments of mutual trust and collaboration but have not yet tested how much influence cultural variables have on each other on collaboration. Therefore this study investigates the effect of the variable of mutual trust on the collaboration variable by using multisample in several industrial sectors in the Greater Bandung Region, Indonesia. The method used is a simple linear regression analysis with SPSS version 17. The research results show that the instruments adopted from both variables show valid results and can replicate in multiple samples in several industrial sectors in the Greater Bandung Region, Indonesia. Furthermore, the results of this study indicate that there is a positive and significant influence between the variables of mutual trust on collaboration.